A retrospective study of internal small bowel herniation following pelvic lymphadenectomy for gynecologic carcinomas - Tanaka, Yuji (Sci Rep, 2021)
After pelvic lymphadenectomy (PLA), pelvic vessels, nerve, and ureter are skeletonized. Internal hernias beneath the skeletonized pelvic structure following pelvic lymphadenectomy (IBSPP) are a rare complication following PLA. To the best of our knowledge, only 12 IBSPP cases have been reported and clinical details on such hernias remain unknown. The aim of the study was to investigate the incident and etiology of IBSPP. 1313 patients who underwent open or laparoscopic pelvic lymphadenectomy were identified from our database. A retrospective review was performed. Mean follow-up period was 33.9 months. A total of 12 patients had IBSPP. Multivariate analysis of laparoscopic surgeries group as compared to open surgeries group, para-aortic lymphadenectomy rate, number of dissected lymph nodes by PLA, antiadhesive material use rate, and blood loss were lower in laparoscopic surgeries group: odd ratio (OR) = 0.13 [95% confidence interval (CI) 0.08–0.19], and OR = 0.70 [95% CI 0.50–0.99], OR = 0.17 [95% CI 0.10–0.28], OR = 0.93 [95% CI 0.92–0.94]. However, no significant difference was observed in the incidence of IBSPP between laparoscopic surgery (1.0%) and open surgery (0.8%). All IBSPP occurred in the right pelvic space. These findings may contribute to the development of prevention methods for this disease.